Composite polymer electrolyte for lithium air battery and preparation method of composite polymer electrolyte
By using conductive polymers, polyethylene oxide, aerogel fillers and lithium electrolytes to prepare composite polymer electrolytes, the problem of poor adaptability and stability of polymer electrolyte matrix in lithium air batteries is solved, and efficient and environmentally friendly battery performance is achieved promote.
Patent Information
- Application Number
- CN202411464518.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-21
- Publication Date
- 2025-02-18
AI Technical Summary
Existing lithium-air batteries lack suitable polymer electrolyte matrix, and single polyethylene oxide or polyvinylidene fluoride has problems with low ionic conductivity, poor stability and the use of toxic solvents.
The composite polymer electrolyte is prepared by dissolution, stirring, ultrasonic dispersion and vacuum drying. Carbon aerogel is used as filler to improve conductivity and structure. Tightness.
The charging and discharging efficiency and cycle stability of lithium air batteries are improved, internal resistance is reduced, and the preparation method is green and environmentally friendly, and no toxic solvent is used.
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of composite materials, and in particular, relates to a method for preparing a composite polymer electrolyte for a lithium-air battery. Background Art
[0002] Energy and environment are two core themes in the development of human society. Breakthroughs in clean and efficient energy conversion and utilization technologies are the key to achieving progress in human society. Lithium-air batteries, which achieve efficient energy conversion and storage based on the reaction between lithium metal and oxygen in the air, have a theoretical energy density of up to 3500Whkg. -1 , which has great research prospects.
[0003] However, lithium-air batteries face many obstacles in the process of achieving performance. Lithium-air batteries lack a suitable polymer electrolyte matrix. Among the lithium battery polymer matrices in the prior art, polyethylene oxide was the earliest studied for polymer electrolytes. The ether oxygen atoms contained in its molecules can effectively absorb electrolytes, but polyethylene oxide has low ionic conductivity at room temperature, and higher temperatures are not conducive to the cycle stability of the battery. Polyvinylidene fluoride is also widely used in the research of polymer electrolytes, but polyvinylidene fluoride has poor solubility and requires a large amount of toxic solvent N-methylpyrrolidone during processing, which is not environmentally friendly. In order to achieve the excellent performance of lithium-air batteries, a polymer electrolyte that is compatible with it is needed. Summary of the invention
[0004] The object of the present invention is to provide a composite polymer electrolyte for lithium-air batteries and a preparation method thereof, so as to solve the problems mentioned in the above background technology.
[0005] The purpose of the present invention can be achieved through the following technical solutions: A composite polymer electrolyte for a lithium-air battery, characterized in that it comprises the following raw materials: a conductive polymer, polyethylene oxide, an aerogel filler, and a lithium electrolyte; A method for preparing a composite polymer electrolyte for a lithium-air battery comprises the following steps: The first step: dissolving the conductive polymer and polyethylene oxide in an organic solvent, adding a lithium electrolyte thereto, and stirring evenly to obtain a composite polymer electrolyte solution; Step 2: adding the aerogel filler into the composite polymer electrolyte solution obtained in the first step, and ultrasonically dispersing to obtain a gel polymer electrolyte; Step 3: Immerse the battery separator in the gel polymer electrolyte obtained in the second step, and vacuum dry to obtain the composite polymer electrolyte.
[0006] Furthermore, the organic solvent used in the first step is one of N,N-dimethylformamide and acetonitrile.
[0007] Furthermore, the lithium electrolyte used in the first step is one of lithium trifluoromethanesulfonate and lithium imide bistrifluoromethanesulfonate.
[0008] Furthermore, in the first step, the mass ratio of the conductive polymer to polyethylene oxide is 0.5-0.8:10.
[0009] Furthermore, in the first step, the stirring speed condition is 700-1000 r / min, and the stirring time condition is 10-12 h.
[0010] Furthermore, the aerogel filler used in the second step is carbon aerogel.
[0011] Furthermore, the time condition of ultrasonic dispersion in the second step is 30-60 min.
[0012] Furthermore, in the third step, the temperature condition of vacuum drying is 50-60° C., and the time condition of vacuum drying is 12 h.
[0013] Further, the conductive polymer is prepared by the following steps: Step 1: 3-aminothieno[2,3-b]pyridine-2-carboxylic acid ethyl ester, N-(chloroformyl) isocyanate, triethylamine and N,N-dimethylformamide were mixed in a three-necked flask, magnetic stirring was started, and the mixture was reacted at room temperature for 4-6 hours. After the reaction was completed, deionized water was added to the three-necked flask for washing, and then the organic layer was separated with a separatory funnel, and the intermediate 1 was obtained by rotary evaporation; Step 2: Mix the intermediate 1, 2-chloroethanol and acetonitrile in a three-necked flask, install a condenser and a thermometer, start magnetic stirring, and react at a temperature of 60-80°C for 10-12h. After the reaction is completed, rotary evaporation is performed to obtain the intermediate 2; Step 3: Mix the intermediate 2, dibutyltin dilaurate and N,N-dimethylformamide in a three-necked flask, install a condenser and a thermometer, turn on the magnetic stirring, raise the system temperature to 80°C, then add benzoyl peroxide to the three-necked flask, and react at 80°C for 4-6h. After the reaction is completed, add deionized water to the three-necked flask for washing, separate the organic layer with a separatory funnel, and rotary evaporate to obtain the conductive polymer.
[0014] Furthermore, the amount ratio of ethyl 3-aminothieno[2,3-b]pyridine-2-carboxylate, N-(chloroformyl)isocyanate, triethylamine, and N,N-dimethylformamide used in step 1 is 0.1 mol: 0.1 mol: 0.12-0.15 mol: 80-100 mL.
[0015] Furthermore, the usage ratio of the intermediate 1,2-chloroethanol and acetonitrile used in step 2 is 0.08 mol: 0.08-0.1 mol: 40-60 mL.
[0016] Furthermore, the usage ratio of intermediate 2, dibutyltin dilaurate, N,N-dimethylformamide and benzoyl peroxide used in step 3 is 0.06 mol: 0.008-0.02 g: 40-60 mL: 0.2 g.
[0017] Beneficial effects of the present invention: The invention uses self-made conductive polymer, polyethylene oxide, aerogel filler and lithium electrolyte as raw materials to prepare a composite polymer electrolyte for lithium-air battery; the invention obtains a composite polymer electrolyte liquid by dissolving the conductive polymer, polyethylene oxide and lithium electrolyte with organic solvent and stirring and mixing, then adds the aerogel filler into the composite polymer electrolyte liquid for ultrasonic dispersion to obtain a gel polymer electrolyte, finally immerses the battery separator in the gel polymer electrolyte, and vacuum dries to obtain a composite polymer electrolyte for lithium-air battery; the invention uses carbon aerogel as aerogel filler, the high conductivity of the carbon aerogel helps to reduce the internal resistance of the composite polymer electrolyte and improve the charge and discharge efficiency of the battery, and its porous structure can also optimize the microstructure of the composite polymer electrolyte, so that the structure of the prepared composite polymer electrolyte is more compact, and the cycle stability of the battery can be effectively improved. At the same time, the composite polymer electrolyte of the invention does not use toxic N-methylpyrrolidone during preparation, and the preparation method is green and environmentally friendly.
[0018] The present invention uses 3-aminothieno[2,3-b]pyridine-2-carboxylic acid ethyl ester and N-(chloroformyl) isocyanate as raw materials, triethylamine as an acid-binding agent, utilizes the amino group of 3-aminothieno[2,3-b]pyridine-2-carboxylic acid ethyl ester and the acyl chloride group of N-(chloroformyl) isocyanate to undergo amidation reaction to obtain intermediate 1, then causes the tertiary amine structure of pyridine in intermediate 1 to undergo quaternary ammonium salt reaction with the chlorine atom of 2-chloroethanol to obtain intermediate 2, and finally causes the isocyanate group and the hydroxyl group of intermediate 2 to undergo quaternary ammonium salt reaction in the presence of a catalyst dibutyl dilaurate. A conductive polymer is obtained by self-polymerization under the catalytic action of tin and initiator benzoyl peroxide; the macromolecular flexibility of the conductive polymer main chain has sufficient ionic power, wherein a large number of carbonyl structures and the π electron cloud conjugated system of the benzene ring and the thiophene ring allow electrons to jump in different molecular orbits, thereby enabling electrons to be freely transmitted in the molecule; after being blended with polyethylene oxide, the conductive polymer of the present invention can effectively solve the problems of low ionic conductivity, narrow working voltage window and poor stability existing in a single polyethylene oxide system.
[0019] The preparation method of the composite polymer electrolyte for a lithium-air battery of the present invention is green and environmentally friendly. The prepared composite polymer electrolyte has a compact structure and small internal resistance, and can effectively improve the charge and discharge efficiency and cycle stability of the lithium-air battery. DETAILED DESCRIPTION
[0020] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Example
[0021] A conductive polymer comprising the following preparation steps: Step 1: 0.1 mol of ethyl 3-aminothieno[2,3-b]pyridine-2-carboxylate, 0.1 mol of N-(chloroformyl)isocyanate, 0.12 mol of triethylamine, and 80 mL of N,N-dimethylformamide were mixed in a container, stirred evenly, and reacted at room temperature for 4 h. After the reaction was completed, deionized water was added to the container for washing, and the organic layer was separated and rotary evaporated to obtain intermediate 1; Step 2: 0.08 mol of intermediate 1, 0.08 mol of 2-chloroethanol and 40 mL of acetonitrile were mixed in a container, stirred evenly, and reacted at 60°C for 10 h. After the reaction was completed, intermediate 2 was obtained by rotary evaporation; Step 3: 0.06 mol of intermediate 2, 0.008 g of dibutyltin dilaurate, and 40 mL of N,N-dimethylformamide were mixed in a container, and after stirring evenly, the system temperature was raised to 80°C, and then 0.2 g of benzoyl peroxide was added to the container, and the reaction was carried out at a temperature of 80°C for 4 hours. After the reaction was completed, deionized water was added to the container for washing, and after separating the organic layer, a conductive polymer was obtained by rotary evaporation. Example
[0022] A conductive polymer comprising the following preparation steps: Step 1: 0.1 mol 3-aminothieno[2,3-b]pyridine-2-carboxylic acid ethyl ester, 0.1 mol N-(chloroformyl) isocyanate, 0.135 mol triethylamine, and 90 mL N,N-dimethylformamide were mixed in a container, stirred evenly, and reacted at room temperature for 5 h. After the reaction was completed, deionized water was added to the container for washing, and the organic layer was separated and rotary evaporated to obtain intermediate 1; Step 2: 0.08 mol of intermediate 1, 0.09 mol of 2-chloroethanol and 50 mL of acetonitrile were mixed in a container, stirred evenly, and reacted at 70°C for 11 h. After the reaction was completed, intermediate 2 was obtained by rotary evaporation; Step 3: 0.06 mol of intermediate 2, 0.014 g of dibutyltin dilaurate, and 50 mL of N,N-dimethylformamide were mixed in a container, and after stirring evenly, the system temperature was raised to 80°C, and then 0.2 g of benzoyl peroxide was added to the container, and the reaction was carried out at a temperature of 80°C for 5 hours. After the reaction was completed, deionized water was added to the container for washing, and after separating the organic layer, a conductive polymer was obtained by rotary evaporation. Example
[0023] A conductive polymer comprising the following preparation steps: Step 1: 0.1 mol of ethyl 3-aminothieno[2,3-b]pyridine-2-carboxylate, 0.1 mol of N-(chloroformyl)isocyanate, 0.15 mol of triethylamine, and 100 mL of N,N-dimethylformamide were mixed in a container, stirred evenly, and reacted at room temperature for 6 h. After the reaction was completed, deionized water was added to the container for washing, and the organic layer was separated and rotary evaporated to obtain intermediate 1; Step 2: 0.08 mol of intermediate 1, 0.1 mol of 2-chloroethanol and 60 mL of acetonitrile were mixed in a container, stirred evenly, and reacted at 80°C for 12 h. After the reaction was completed, intermediate 2 was obtained by rotary evaporation; Step 3: 0.06 mol of intermediate 2, 0.02 g of dibutyltin dilaurate, and 60 mL of N,N-dimethylformamide were mixed in a container, and after stirring evenly, the system temperature was raised to 80°C, and then 0.2 g of benzoyl peroxide was added to the container, and the reaction was carried out at a temperature of 80°C for 6 hours. After the reaction was completed, deionized water was added to the container for washing, and after separating the organic layer, a conductive polymer was obtained by rotary evaporation. Example
[0024] A composite polymer electrolyte for a lithium-air battery, characterized in that it comprises the following raw materials: the conductive polymer obtained in Example 1, polyethylene oxide, carbon aerogel, and lithium trifluoromethanesulfonate; A method for preparing a composite polymer electrolyte for a lithium-air battery comprises the following steps: Step 1: Dissolve the conductive polymer and polyethylene oxide obtained in Example 1 in N,N-dimethylformamide, add lithium trifluoromethanesulfonate thereto, and stir at a speed of 700 r / min for 10 hours to obtain a composite polymer electrolyte solution; Step 2: adding the carbon aerogel to the composite polymer electrolyte solution obtained in the first step, and ultrasonically dispersing for 30 minutes to obtain a gel polymer electrolyte; Step 3: Immerse the battery separator in the gel polymer electrolyte obtained in the second step, and vacuum dry it at 50°C for 12 hours to obtain a composite polymer electrolyte for lithium-air batteries.
[0025] Wherein, in the first step, the mass ratio of the conductive polymer obtained in Example 1 to polyethylene oxide is 0.5:10. Example
[0026] A composite polymer electrolyte for a lithium-air battery, characterized in that it comprises the following raw materials: the conductive polymer obtained in Example 2, polyethylene oxide, carbon aerogel, and lithium trifluoromethanesulfonate; A method for preparing a composite polymer electrolyte for a lithium-air battery comprises the following steps: Step 1: dissolving the conductive polymer and polyethylene oxide obtained in Example 2 in acetonitrile, adding lithium trifluoromethanesulfonate thereto, and stirring at a speed of 850 r / min for 11 hours to obtain a composite polymer electrolyte solution; Step 2: adding the carbon aerogel to the composite polymer electrolyte solution obtained in the first step, and ultrasonically dispersing for 45 minutes to obtain a gel polymer electrolyte; Step 3: Immerse the battery separator in the gel polymer electrolyte obtained in the second step, and vacuum dry it at a temperature of 55° C. for 12 hours to obtain a composite polymer electrolyte for lithium-air batteries.
[0027] Wherein, in the first step, the mass ratio of the conductive polymer obtained in Example 2 to polyethylene oxide is 0.65:10. Example
[0028] A composite polymer electrolyte for a lithium-air battery, characterized in that it comprises the following raw materials: the conductive polymer obtained in Example 3, polyethylene oxide, carbon aerogel, and lithium bis(trifluoromethanesulfonate imide); A method for preparing a composite polymer electrolyte for a lithium-air battery comprises the following steps: Step 1: Dissolve the conductive polymer and polyethylene oxide obtained in Example 3 in N,N-dimethylformamide, add lithium imide bistrifluoromethanesulfonate thereto, and stir at a speed of 1000 r / min for 12 hours to obtain a composite polymer electrolyte solution; Step 2: adding the carbon aerogel to the composite polymer electrolyte solution obtained in the first step, and ultrasonically dispersing for 60 minutes to obtain a gel polymer electrolyte; Step 3: Immerse the battery separator in the gel polymer electrolyte obtained in the second step, and vacuum dry it at 60°C for 12 hours to obtain a composite polymer electrolyte for lithium-air batteries.
[0029] Wherein, in the first step, the mass ratio of the conductive polymer obtained in Example 3 to polyethylene oxide is 0.8:10.
[0030] Comparative Example 1 The raw material "conductive polymer obtained in Example 3" used in Example 6 was removed, and the other raw materials and preparation steps remained unchanged.
[0031] Comparative Example 2 This comparative example is a lithium battery separator sold by Dalian Guomao Materials Technology Co., Ltd.
[0032] Lithium-air batteries were assembled using the composite polymer electrolytes for lithium-air batteries obtained in Examples 4-6 and Comparative Example 1 and lithium battery separators sold by Dalian Guomao Materials Technology Co., Ltd. and then subjected to cycle stability tests. The test results are shown in Table 1.
[0033] Cycle stability test: The number of stable charge and discharge cycles of the battery at a cutoff specific capacity of 500mAh / mL and a current density of 1mA / mL was tested at room temperature and 50°C.
[0034] Table 1 It can be seen from Table 1 that the composite polymer electrolyte for lithium-air batteries of the present invention can effectively improve the cycle stability of lithium-air batteries. This is because the carbon aerogel used in the present invention makes the composite polymer electrolyte structure more compact, while Comparative Example 1 still uses a single polymer system, so the cycle stability is poor. This shows that the composite polymer electrolyte of the present invention can solve the problem of poor stability of a single polymer system and has a good prospect for use.
[0035] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.
Claims
1. A composite polymer electrolyte for a lithium-air battery, characterized in that: Contains the following raw materials: conductive polymer, polyethylene oxide, aerogel filler, lithium electrolyte; Wherein, the conductive polymer is prepared by the following steps: Step 1: 3-aminothieno[2,3-b]pyridine-2-carboxylic acid ethyl ester, N-(chloroformyl)isocyanate, triethylamine and N,N-dimethylformamide are mixed in a container, stirred evenly, and reacted at room temperature for 4-6 hours to obtain intermediate 1; Step 2: Mix the intermediate 1, 2-chloroethanol and acetonitrile in a container, stir evenly, and react at 60-80° C. for 10-12 h to obtain the intermediate 2; Step 3: Mix the intermediate 2, dibutyltin dilaurate and N,N-dimethylformamide in a container, stir evenly, raise the system temperature to 80°C, then add benzoyl peroxide to the container, and react at 60°C for 4-6h to obtain the conductive polymer.
2. A composite polymer electrolyte for lithium-air batteries according to claim 1, characterized in that: The amount ratio of ethyl 3-aminothieno[2,3-b]pyridine-2-carboxylate, N-(chloroformyl)isocyanate, triethylamine, and N,N-dimethylformamide used in step 1 is 0.1 mol: 0.1 mol: 0.12-0.15 mol: 80-100 mL.
3. A composite polymer electrolyte for lithium-air batteries according to claim 1, characterized in that: The amount ratio of the intermediate 1, 2-chloroethanol and acetonitrile used in step 2 is 0.08 mol: 0.08-0.1 mol: 40-60 mL.
4. A composite polymer electrolyte for lithium-air batteries according to claim 1, characterized in that: The usage ratio of intermediate 2, dibutyltin dilaurate, N,N-dimethylformamide and benzoyl peroxide used in step 3 is 0.06 mol: 0.008-0.02 g: 40-60 mL: 0.2 g.
5. A method for preparing a composite polymer electrolyte for a lithium-air battery, characterized in that: The following steps are involved: The first step is to dissolve the conductive polymer and polyethylene oxide in an organic solvent, add lithium electrolyte thereto, and stir evenly to obtain a composite polymer electrolyte solution; Step 2: adding the aerogel filler into the composite polymer electrolyte solution obtained in the first step, and ultrasonically dispersing to obtain a gel polymer electrolyte; Step 3: Immerse the battery separator in the gel polymer electrolyte obtained in the second step, and vacuum dry to obtain the composite polymer electrolyte.
6. The method for preparing a composite polymer electrolyte for a lithium-air battery according to claim 5, characterized in that: The organic solvent used in the first step is one of N,N-dimethylformamide and acetonitrile, the lithium electrolyte used is one of lithium trifluoromethanesulfonate and lithium bistrifluoromethanesulfonate imide, and the mass ratio of the conductive polymer to polyethylene oxide is 0.5-0.8:
10.
7. The method for preparing a composite polymer electrolyte for a lithium-air battery according to claim 5, characterized in that: In the first step, the stirring speed condition is 700-1000r / min, and the stirring time condition is 10-12h.
8. The method for preparing a composite polymer electrolyte for a lithium-air battery according to claim 5, characterized in that: The aerogel filler used in the second step is carbon aerogel.
9. The method for preparing a composite polymer electrolyte for a lithium-air battery according to claim 5, characterized in that: The time condition of ultrasonic dispersion in the second step is 30-60min.
10. The method for preparing a composite polymer electrolyte for a lithium-air battery according to claim 5, characterized in that: In the third step, the temperature condition of vacuum drying is 50-60°C, and the time condition of vacuum drying is 12h.